Prenatal Diagnosis of Persistent Hyperplastic Primary Vitreous: Report of 2 Cases and Review of the Literature. (1st October 2016) - Esmer, Aytul Corbacioglu; Sivrikoz, Tugba Sarac; Gulec, Elif Yilmaz; Sezer, Salim; Kalelioglu, Ibrahim; Has, Recep; Yuksel, Atil
Abstract : Persistent hyperplastic primary vitreous is a spectrum of congenital ocular abnormalities characterized by leukocoria, microphthalmia, cataracts, extensive intravitreal hemorrhage, persistence of the hyaloid artery, glaucoma, and retinal detachment. It might be isolated or associated with congenital syndromes such as trisomy 13, Walker‐Warburg syndrome, and Norrie disease. We present 2 cases of persistent hyperplastic primary vitreous diagnosed by prenatal sonography in the early third trimester. Bilateral hyperechoic lenses and retinal nonattachment were detected in the sonographic examination of the first case, whereas irregular echogenic bands between the lenses and posterior walls of the eyes were prominent in the second case. In both of the cases, ocular findings were accompanied by intracranial findings, including severe hydrocephalus, an abnormal gyral pattern, and cerebellar hypoplasia, suggesting the diagnosis of Walker‐Warburg syndrome. We also present a review of the literature regarding the prenatal diagnosis of this malformation.